Serum IL-6 correlates with axial mobility index (Bath Ankylosing Spondylitis Metrology Index) in Brazilian patients with ankylosing spondylitis - Rabelo CF (Dove Medical Press, 2018)
Cristina F Rabelo,1 Talita Siara Almeida Baptista,2 Laura Esteves Petersen,2 Moisés Evandro Bauer,2 Mauro Waldemar Keiserman,1 Henrique Luiz Staub1 1Department of Rheumatology, 2Laboratory of Immunosenescence, Institute of Biomedical Research, Pontifical Catholic University of Rio Grande do Sul (PUCRS), Porto Alegre, Brazil Introduction: Ankylosing spondylitis (AS) is a chronic disease featuring axial changes, peripheral arthritis and systemic involvement. Proinflammatory cytokines are probably involved in AS pathogenesis. The relationship of circulating cytokines with instruments of AS evaluation is an open field of research.Objective: The aim of this study was to compare serum levels of cytokines in AS patients and healthy controls, and search for correlations of cytokines with indexes of disease activity and quality of life.Patients and methods: In this cross-sectional study, 32 AS patients and 32 age- and sex-matched controls were evaluated. Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Funcional Index (BASFI), Bath Ankylosing Spondylitis Metrology Index (BASMI), Ankylosing Spondylitis Disease Activity Score-C reactive protein (ASDAS-CRP), Maastricht Ankylosing Spondylitis Enthesitis Score (MASES), Ankylosing Spondylitis Quality of Life (ASQol) and Patient Global Assessment score were measured in AS patients. . The soluble cytokines IL-6, IL-8, IL-1, IL-10, TNF-α, IL-12p70 and IL-17 were quantified by flow cytometry. IL-23 concentrations were measured using an enzyme-linked immunosorbent assay.Results: Overall, AS patients were predominantly males (59.4%) and Caucasians (96.9%). Mean age was 46.9±10.7 years. Human leukocyte antigen B27 was present in 70% of cases. Concentrations of IL-6, IL-8, IL-10 and TNF-α were higher in AS cases than controls (p<0.05). Mean concentration of IL-6 correlated with the BASMI, an index of axial mobility (r=0.354, p=0.047). Anti-TNF intake (present in 21 patients, 65.6%) associated with a high BASMI (p=0.042) and lower quality of life as measured using the ASQol scale (p=0.009).Conclusion: A proinflammatory cytokine profile predominated in AS patients, but interestingly, the IL-10 concentrations were also elevated, pointing to a suppressive control of inflammation. A defined correlation of serum IL-6 with the BASMI suggests a role for this cytokine in axial disease. Anti-TNF users showed more axial activity and lower quality of life. Keywords: ankylosing spondylitis, cytokines, disease activity index, quality-of-life score, BASMI